(untitled) (Eurasian Medical Research Periodical, 2024)
Despite significant progress in the development and improvement of methods of treatment of ectopic pregnancy, the problem of further rehabilitation of reproductive function remains extremely relevant and requires further study. The issues of etiology, pathogenesis, diagnosis and treatment of ectopic pregnancy have been studied in sufficient detail. Nevertheless, a number of issues remain unresolved.